2022
DOI: 10.1080/10803548.2022.2115657
|View full text |Cite
|
Sign up to set email alerts
|

Improving the antecedents of non-compliance to safety regulations toward an optimized self-regulated construction environment in Nigeria

Abstract: The construction industry has been plagued with safety challenges, resulting in a wide occurrence of devastating accidents and fatalities. As previous studies have attributed the persistent safety challenges in Nigeria to non-compliance to safety regulations, this study builds on the existing literature by assessing the antecedents of non-compliance to safety regulations amongst construction workers. To achieve this, the study pursued two main objectives which involved the assessment of workers' safety attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Higher income and education levels are associated with better safety compliance and training effectiveness, as these factors enhance employees' ability to understand and adhere to safety protocols as highlighted by Soliman and Altabtai [66] and Wilkins [67]. Additionally, effective regulatory enforcement promotes a culture of accountability and compliance, leading to improved adherence to safety guidelines and the effectiveness of training programs, as observed in studies by Othman [105] and Zailani et al [71].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Higher income and education levels are associated with better safety compliance and training effectiveness, as these factors enhance employees' ability to understand and adhere to safety protocols as highlighted by Soliman and Altabtai [66] and Wilkins [67]. Additionally, effective regulatory enforcement promotes a culture of accountability and compliance, leading to improved adherence to safety guidelines and the effectiveness of training programs, as observed in studies by Othman [105] and Zailani et al [71].…”
Section: Discussionmentioning
confidence: 94%
“…Research indicates that strong regulatory frameworks improve compliance with safety standards [26][27][28]71]. Effective government regulations ensure that safety guidelines are followed, thereby enhancing overall safety adherence on construction sites.…”
Section: H4 Communication Styles (Css) Positively Influence Asgsmentioning
confidence: 99%
“…Caregivers who recognise the importance of proper ventilation and the necessity of reading product labels are likely more cautious about safety and, consequently, engage in safer practices. Research in other contexts has similarly shown that caregiver's attitudes toward safety signi cantly in uence their behavior [42,46,47]. For example, studies on poisoning have found that mothers with a positive attitude were more likely to engage in better behaviours [42,46].…”
Section: Discussionmentioning
confidence: 99%